Diverticular disease of the colon - Ehrmann-Jóśko, Agnieszka (Przewodnik Lekarza/Guide for GPs, 2005)
Diverticula are acquired protrusions of the colonic wall. They are consist only mucosa and submucosa of the colonic wall. Diverticulosis refers to the presence of one or more diverticula on the colon. Diverticula may be distributed throughout the colon, but never in the rectum, and are most frequently located in the sigmoid colon. An increased risk of developing diverticular disease is associated with a low alimentary fibre and a diet high in red meat and total fat content. Colonic divertculosis affects approximately 50% people in the ninth decade of life. The disease has a clinical spectrum from asymptomatic to symptomatic disease with potentially dangerous complications: bleeding, perforation and peritonitis, being fistulae and abscess.